2017
DOI: 10.1002/aic.15634
|View full text |Cite
|
Sign up to set email alerts
|

High performance of la‐promoted Fe2O3/α‐Al2O3oxygen carrier for chemical looping combustion

Abstract: Iron oxide supported oxygen carrier (OC) is regarded to a promising candidate for chemical looping combustion (CLC). However, phase separation between Fe2O3 and supports often occurs resulted from the severe sintering of supports during calcination, which leads to the sintering and breakage of Fe2O3 thus the decrease of redox reactivity. In this article, La‐promoted Fe2O3/α‐Al2O3 were used as OCs for CLC of CH4 and for the first time found that the OC with the addition of 18 wt % La exhibited outstanding react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The large amount of CO 2 emission as a result of excessively relying on the combustion of fossil fuels leads to global warming. , Some techniques, such as pre-combustion, post-combustion, and oxy-fuel combustion, have been studied for CO 2 capture and separation, which suffered from the high operating costs of gas separation processes. The shortcoming of the above techniques could result in a significant decrease in the overall combustion efficiency and an increase in the price of the energy. As a new advanced CO 2 capture technique, chemical looping combustion (CLC) has been extensively investigated to avoid the costly gas separation. , In the CLC process, fuels are reacted with lattice oxygen provided by the oxygen carrier (OC) and the main products are CO 2 and H 2 O after the complete combustion.…”
Section: Introductionmentioning
confidence: 99%
“…The large amount of CO 2 emission as a result of excessively relying on the combustion of fossil fuels leads to global warming. , Some techniques, such as pre-combustion, post-combustion, and oxy-fuel combustion, have been studied for CO 2 capture and separation, which suffered from the high operating costs of gas separation processes. The shortcoming of the above techniques could result in a significant decrease in the overall combustion efficiency and an increase in the price of the energy. As a new advanced CO 2 capture technique, chemical looping combustion (CLC) has been extensively investigated to avoid the costly gas separation. , In the CLC process, fuels are reacted with lattice oxygen provided by the oxygen carrier (OC) and the main products are CO 2 and H 2 O after the complete combustion.…”
Section: Introductionmentioning
confidence: 99%
“…As for the doped CeO 2 as supports for active metal oxides in the chemical looping process, Bhavsar et al found that La-doped CeO 2 could increase the oxygen transfer capacity and improve the activity and recyclability of iron oxygen carrier. Moreover, La-doped Fe 2 O 3 /Al 2 O 3 can significantly improve the activity and recyclability for the chemical looping combustion (CLC) and partial oxidation of CH 4 by CO 2 due to the generation of La-hexaaluminate. , Hedayati et al . indicated that the metal oxides with Ce 0.9 Gd 0.1 O 1.9 as support were more active than those with CeO 2 in CLC, demonstrating satisfactory sintering and agglomeration resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Materials such as perovskites and spinels are widely applied for this process, because of their stable oxygen storage capacity and high oxygen mobility . In a novel chemical looping application, Fe 2 O 3 /MgAl 2 O 4 spinel was used as an energy storage material and Ni/MgAl 2 O 4 as dry reforming catalyst, next to CaO/Al 2 O 3 as sorbent material for CO 2 capture.…”
Section: Introductionmentioning
confidence: 99%